Under a Watchful Eye: A Case Study of Police Surveillance During the 1930s - Lonardo, Michael (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1995)
During the 1930s the Communist Party of Canada organized and promoted the working-class struggle against conditions resulting from the Depression. And while some have argued that the state's intelligence community paid little attention to the efforts of the communists between the wars, the evidence reveals a major operation on the part of the Royal Canadian Mounted Police to watch and suppress Communist Party activities. By tracing the involvement of World War I veteran and Communist Party activist, Stewart O'Neil, in four radical movements — the Workers Ex-Servicemen's League, the On-to-Ottawa trek, the workers' theatre movement, and the Spanish Civil War— this paper demonstrates the extent of, and the tactics used by the RCMP in its surveillance and suppression of these radical movements.